Hambatan Pemenuhan Hak-Hak Anak sebagai Pelaku Tindak Pidana Pelecehan Seksual di LPKA Kelas II Yogyakarta - Kumaladewi, Qurrota Ayunin; Laras Astuti (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
Currently, children are not only victims of sexual abuse but also perpetrators, so they must be held accountable for the consequences of their actions at Special Child Guidance Institutions (LPKA), one of which is the LPKA in Yogyakarta. At the LPKA, children, as perpetrators, still receive their full rights as children, even though there are limitations and differences in their implementation. Based on this, this paper will further discuss the obstacles that affect the fulfillment of children's rights at the LPKA. The research method used is normative empirical, with data collection techniques through interviews, observation, questionnaires, and documentation studies. The results of the study show that the LPKA in Yogyakarta strives to create an environment that supports the rehabilitation and reintegration of child offenders, but the main obstacles affecting the fulfillment of children's rights in an education, health and recreation include limited facilities, a lack of competent professionals, and constraints in the existing system. This paper recommends the need for improvements in regulations, facilities, and existing systems to optimize the fulfillment of children's rights at the LPKA in Yogyakarta